Effects of Aquaculture on Lakes in the Central Yangtze River Basin, China, II: Benthic Macroinvertebrates. (17th August 2018) - Qu, Xiao; Xia, Wengtong; Wang, Rui; Zhang, Yingxue; Xie, Zhicai; Trushenski, Jesse; Chen, Yushun
Abstract: There is limited information available on the effects of extensive aquaculture or "fish ranching" operations on lake ecosystems. To study the effects of aquaculture on lake ecosystems, benthic macroinvertebrate communities were investigated from July to September 2015 in 23 lakes within the middle reach of the Yangtze River basin. The lakes represented four lake management strategies: fish ranching supported by low (LOW), medium (MEDIUM), or high (HIGH) stocking rates; or fallowing (FALLOW) in which previously ranched HIGH lakes had not been stocked for 2 years. Total macroinvertebrate densities did not vary significantly but were highest in the FALLOW lakes (2, 352 individuals/m 2 ), lowest in the LOW lakes (544 individuals/m 2 ), and intermediate in the HIGH (1, 734 individuals/m 2 ) and MEDIUM lakes (1, 208 individuals/m 2 ). Chironomid densities were significantly lower in LOW lakes compared to all others, and mollusks were not observed in LOW lakes. Chironomid and total macroinvertebrate biomasses were also significantly lower in LOW lakes than in the other lakes. The FALLOW lakes had significantly greater biomasses of mollusks, oligochaetes, and total macroinvertebrates than all other lakes. Two pollution‐tolerant taxa, Tubificidae and Chironomidae, were dominant in all lakes regardless of management strategy, indicating that all study lakes were experiencing some degree of eutrophication. Results indicated that fish ranching does not affect macroinvertebrate communities in a predictable manner based on stocking density, but allowing for a fallowing period could potentially benefit lake macroinvertebrates. Canonical correspondence analysis indicated that chlorophyll a, chloride, conductivity, and total nitrogen were affecting macroinvertebrate density in these lakes, while total suspended solids, alkalinity, turbidity, total hardness, and water depth affected macroinvertebrate biomass.